2014
DOI: 10.3389/fnagi.2014.00140
|View full text |Cite
|
Sign up to set email alerts
|

Aging induced loss of complexity and dedifferentiation: consequences for coordination dynamics within and between brain, muscular and behavioral levels

Abstract: Growing evidence demonstrates that aging not only leads to structural and functional alterations of individual components of the neuro-musculo-skeletal system (NMSS) but also results in a systemic re-organization of interactions within and between the different levels and functional domains. Understanding the principles that drive the dynamics of these re-organizations is an important challenge for aging research. The present Hypothesis and Theory paper is a contribution in this direction. We propose that age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 169 publications
(270 reference statements)
9
73
0
3
Order By: Relevance
“…In other words, the results might suggest that the set of dynamical repertoires used is the same between age groups but elderly do not switch between them as often or alternatively that a smaller set of dynamical repertoires is available. Only the latter case would be consistent with the dedifferentiation hypotheses (Sleimen-Malkoun et al, 2014) which was also found for the kinematic data presented here. The analyses of muscular synergies allowed answering this question.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In other words, the results might suggest that the set of dynamical repertoires used is the same between age groups but elderly do not switch between them as often or alternatively that a smaller set of dynamical repertoires is available. Only the latter case would be consistent with the dedifferentiation hypotheses (Sleimen-Malkoun et al, 2014) which was also found for the kinematic data presented here. The analyses of muscular synergies allowed answering this question.…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, aging is a dynamic process that presents itself with both alterations within all subsystems—though each having their individual timescale—and with changes in their couplings (e.g., Sleimen-Malkoun et al, 2014). These changes lie at the origin of an age-related loss of behavioral adaptability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reductions in dFC speed and complexity correlate with the level of general cognitive and behavioural performance, as probed by both standard clinical assessments of cognitive impairments (Nasreddine et al, 2005) and a simple visuomotor coordination task (Houweling et al, 2008). The fact that slowing down and complexity loss in dFC are associated with degraded performance can be linked to prominent theories of cognitive aging, speculatively establishing alterations of dFC random walk properties as novel imaging correlates of processing speed reduction (Salthouse, 1996;Finkel et al, 2007) and de-differentiation (Baltes, 1980;Sleimen-Malkoun et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…From the point of view of chaos theory, multiscale and non-linear complexity (structure and interactions of individual subsystems) appears to degrade with ageing and disease [47]. The structures and functions of the individual subsystems are not only affected by the process but also the interactions between them [48]. For this reason, the loss of complexity has even been hypothesized to be an indicator of the transition from normal ageing to frailty [49].…”
Section: Fractal Dimension and Ageingmentioning
confidence: 99%